Pergošić's Translation of the Tripartitum into Slavonian - Štefanec, Nataša (Array, 2003)
The article attempted to reconstruct the motives for the translation and printing of Slavonian version of Werboezcy's Tripartitum, reasons for several distinct remaining copies of the same translation and connections of Ivan Pergošić and Varaždin officials and surrounding nobility, namely the Zrinski family.